Cover Feature: Effects of Film Formation on the Electrodeposition of Lithium (ChemElectroChem 21/2020). Issue 21 (29th September 2020) - Yoshii, Kazuki; Kiuchi, Hisao; Taguchi, Noboru; Shikano, Masahiro; Matsubara, Eiichiro; Sakaebe, Hikari
Abstract : The Cover Feature illustrates the morphology of electrodeposited lithium using 1.0 mol dm −3 LiPF6 /PC electrolyte with and without a trace amount of water. The electrochemical behavior during galvanostatic deposition and morphology of the deposited metallic lithium were dependent on the amount of water and the elapsed time after the addition of water to the electrolyte. More information can be found in the Article by K. Yoshii et al .